Penyuluhan Dan Pelatihan Keselamatan, Kesehatan, Kerja (K3) Serta Latihan Gerak Aktif Sebagai Upaya Preventif Herniated Nucleus Pulposus Dalam Meningkatkan Produktivitas Kerja Petani di Desa Susut Kabupaten Bangli - I Nyoman Bagus Pramartha; Deviana; Sekiguchi Kan (Universitas Mataram, 2020)
The main problem faced by partners is the lack of understanding related to occupational health and safety when carrying out work in agriculture. The possibility of accidents while working to manage rice fields often occurs and farmers do not fully understand the standards of occupational health and safety so the purpose of this service activity is to improve farmers' understanding of occupational health and safety standards as a preventive effort to prevent herniated nucleus pulposus in increasing farmers' work productivity. This activity was carried out in Susut Village, Bangli Regency using counseling and training methods involving 21 farmers. The stage of implementation of activities is divided into four parts, namely; planning stage, implementation stage, monitoring stage and evaluation stage. Evaluation is carried out by providing a questionnaire and looking at the values before and after the activity. Based on the results of the analysis of activities showed the results that; 1) there was an increase in knowledge related to occupational safety and health by 61.91%, 2) there was an increase in the understanding and implementation of active motion as a preventive effort to prevent herniated nucleus pulposus by 90.69%, (3) the work productivity of farmers was known to increase in farm yields by 25.50% after the farmers apply the principles of occupational health and safety (K3). The partner's response to this service activity is very positive and it is hoped that this will continue on an ongoing basis.